Enhanced flux pinning in YBCO multilayer films with BCO nanodots and segmented BZO nanorods - Malmivirta M; Rijckaert H; Paasonen V; Huhtinen H; Hynninen T; Jha R; Awana VS; Van Driessche I; Paturi P (NATURE PUBLISHING GROUP, 2022)
The flux pinning properties of the high temperature superconductor YBa2Cu3O7-d (YBCO) have been conventionally improved by creating both columnar and dot-like pinning centres into the YBCO matrix. To study the effects of differently doped multilayer structures on pinning, several samples consisting of a multiple number of individually BaZrO3 (BZO) and BaCeO3 (BCO) doped YBCO layers were fabricated. In the YBCO matrix, BZO forms columnar and BCO dot-like defects. The multilayer structure improves pinning capability throughout the whole angular range, giving rise to a high critical current density, J(c). However, the BZO doped monolayer reference still has the most isotropic J(c). Even though BZO forms nanorods, in this work the samples with multiple thin layers do not exhibit a c axis peak in the angular dependence of J(c). The angular dependencies and the approximately correct magnitude of J(c) were also verified using a molecular dynamics simulation.